2016
DOI: 10.1155/2016/5061640
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 7-Day and 14-Day Triple Therapy Regimens for the Eradication ofHelicobacter pylori: A Comparative Study in a Cohort of Romanian Patients

Abstract: Objective. This study compared the eradication rates of of Helicobacter pylori (HP) infection by a 7-day and 14-day anti-HP regimen. Materials and Methods. An open, randomized, prospective study was performed to evaluate the response to anti-HP treatment in adult HP-positive patients following a 7-day course (Regimen A) of a proton pump inhibitor in association with clarithromycin and amoxicillin compared to a 14-day course (Regimen B). Gastric biopsies were performed at baseline and two months after anti-HP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…These studies also showed a higher eradication rate using a 10-day therapeutic regimen than a 7-day regimen by approximately 4%; the 14-day regimen had an increased rate by approximately 5%-6% compared with the 7-day regimen. Other studies have confirmed these results (349)(350)(351)(352) , and a recent Cochrane review showed that irrespective of the type and dose of antibiotics, increasing the duration of triple therapy with PPIs from 7 to 14 days significantly increased the rate of eradication of HP (45 studies, 72.9% vs. 81.9%) (348) . Considering this evidence, extension of the duration of triple therapies containing clarithromycin for 14 days was incorporated into the main guidelines on anti-HP therapy (40,(353)(354)(355) .…”
Section: Level Of Evidence: 2amentioning
confidence: 74%
“…These studies also showed a higher eradication rate using a 10-day therapeutic regimen than a 7-day regimen by approximately 4%; the 14-day regimen had an increased rate by approximately 5%-6% compared with the 7-day regimen. Other studies have confirmed these results (349)(350)(351)(352) , and a recent Cochrane review showed that irrespective of the type and dose of antibiotics, increasing the duration of triple therapy with PPIs from 7 to 14 days significantly increased the rate of eradication of HP (45 studies, 72.9% vs. 81.9%) (348) . Considering this evidence, extension of the duration of triple therapies containing clarithromycin for 14 days was incorporated into the main guidelines on anti-HP therapy (40,(353)(354)(355) .…”
Section: Level Of Evidence: 2amentioning
confidence: 74%
“…[30][31][32][33] However, there was no difference regarding the rate of side effects. More recent articles have also disclosed a benefit of prolonging the length of triple therapy, [34][35][36] whereas only a few could not demonstrate an advantage for this strategy. 37,38 Accordingly, the Maastricht V Consensus Report stated that "the treatment duration of PPI-clarithromycin-based triple therapy should be extended to 14 days, unless shorter therapies are proven effective locally".…”
Section: Duration Of Treatmentmentioning
confidence: 99%
“…A number of studies looked at the role that standard triple therapy can play in H. pylori eradication treatment. Three randomised, prospective studies focused on comparing various durations of therapy and all found superior, although less than satisfactory rates of eradication when longer courses of triple therapy were used . The results are outlined in Table .…”
Section: Triple Therapymentioning
confidence: 99%
“…Three randomised, prospective studies focused on comparing various durations of therapy and all found superior, although less than satisfactory rates of eradication when longer courses of triple therapy were used. [17][18][19] The results are outlined in Table 2. A different strategy was pursued in a study from Italy where high dose amoxicillin (1 g t.i.d.)…”
Section: Triple Therapymentioning
confidence: 99%